Critical Role for the Host GTPase-Activating Protein ARAP2 in InlB-Mediated Entry of Listeria monocytogenes - Gavicherla, Balramakrishna (American Society for Microbiology (ASM), 2010)
The bacterial pathogen Listeria monocytogenes causes food-borne illnesses culminating in gastroenteritis, meningitis, or abortion. Listeria induces its internalization into some mammalian cells through binding of the bacterial surface protein InlB to the host receptor tyrosine kinase Met. Interaction of InlB with the Met receptor elicits host downstream signaling pathways that promote F-actin cytoskeletal changes responsible for pathogen engulfment. Here we show that the mammalian signaling protein ARAP2 plays a critical role in cytoskeletal remodeling and internalization of Listeria. Depletion of ARAP2 through RNA interference (RNAi) caused a marked inhibition of InlB-mediated F-actin rearrangements and bacterial entry. ARAP2 contains multiple functional domains, including a GTPase-activating protein (GAP) domain that antagonizes the GTPase Arf6 and a domain capable of binding the GTPase RhoA. Genetic data indicated roles for both the Arf GAP and RhoA binding domains in Listeria entry. Experiments involving Arf6 RNAi or a constitutively activated allele of Arf6 demonstrated that one of the ways in which ARAP2 promotes bacterial uptake is by restraining the activity of Arf6. Conversely, Rho activity was dispensable for Listeria internalization, suggesting that the RhoA binding domain in ARAP2 acts by engaging a host ligand other than Rho proteins. Collectively, our findings indicate that ARAP2 promotes InlB-mediated entry of Listeria, in part, by antagonizing the host GTPase Arf6.